2020
DOI: 10.1002/jia2.25512
|View full text |Cite
|
Sign up to set email alerts
|

Condom use among young women who sell sex in Zimbabwe: a prevention cascade analysis to identify gaps in HIV prevention programming

Abstract: IntroductionAdolescent girls and young women (AGYW), including those who sell sex in sub‐Saharan Africa, are especially vulnerable to HIV. Reaching them with effective prevention is a programmatic priority. The HIV prevention cascade can be used to track intervention coverage, and identify gaps and opportunities for programme strengthening. The aim of this study was to characterise gaps in condom use and identify reasons underlying these gaps among young women who sell sex (YWSS) in Zimbabwe using data from en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The SHG intervention was delivered as part of Zimbabwe’s nationally scaled HIV prevention and treatment programme for sex workers Sisters with a Voice (Sisters) , which offers a wide range of social and clinical services for high-risk women, including AGYW [ 19 , 22 , 26–29 ]. The intervention was delivered in four high-density communities in Harare, Zimbabwe, characterised by small, clustered houses shared by several families, low education levels of resident adults, low-wage and informal employment, and high turnover of residents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SHG intervention was delivered as part of Zimbabwe’s nationally scaled HIV prevention and treatment programme for sex workers Sisters with a Voice (Sisters) , which offers a wide range of social and clinical services for high-risk women, including AGYW [ 19 , 22 , 26–29 ]. The intervention was delivered in four high-density communities in Harare, Zimbabwe, characterised by small, clustered houses shared by several families, low education levels of resident adults, low-wage and informal employment, and high turnover of residents.…”
Section: Methodsmentioning
confidence: 99%
“…In Zimbabwe, high numbers of AGYW experience both early childbearing and HIV risk, many as a result of their involvement in exchanging sex for money or material benefits [ 19 , 20 ]. Nationally, 21.6% of all girls aged 15–19 have begun childbearing, and this is higher among those in the lowest wealth quintile (33.6%) and with primary or lower education (37.8%); by age 25, 91% of the women have given birth at least once [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that poorer mental health (especially severe depression, depression and PTSD, or anxiety) was associated with less consistent condom use or less perceived condom self-efficacy among MSM [80], young women who sold sex [81], and homeless men who also used drugs and traded sex [82]. Condom use self-efficacy and depression were partial mediators of the relationship between sexual stigma and inconsistent condom use among MSM [83].…”
Section: The Relationship Of Mental Health To Hiv Prevention Behavioursmentioning
confidence: 99%
“…Pressure from clients and the inability to negotiate condom use may be more difficult for younger sex workers. 32 Women in Zimbabwe FGDs reported fear of loss of income if they refused to engage in sex without protection/ contraceptives. Related, women in LMIC participating in the online survey were also more likely to value contraceptives that are discreet, so that they did not need to disclose to clients that they were avoiding pregnancy or to negotiate condom use.…”
Section: Discussionmentioning
confidence: 99%